2013
DOI: 10.4236/jst.2013.31001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Sensitivity of Luminescent Epitaxial Surface InP Quantum Dots

Abstract: Surface InP quantum dots grown by gas source molecular beam epitaxy on In 0.48 Ga 0.52 P buffer layer lattice matched to GaAs substrate shows a broad-band near-infrared photoluminescence ranging from 750 to 865 nm dependent on their dimensions. A reversible luminescence intensity enhancement has been observed when the quantum dots were exposed to vapours of different chemical solvents with the highest sensitivity for alcohol (methanol and ethanol) vapours. The luminescent behaviour is dependent on the solvent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
1
6
0
1
Order By: Relevance
“…Such an effect is particularly evident for methanol where a 15% enhancement of the fast decay time has been measured. The results are fully compatible with a model we recently suggested [8,16,18] based on the saturation effect of the QD non-radiative surface states by the vapour organic molecules. The model suggested is here experimentally confirmed for the first time while the alternative explanation of an off-set of the air potential barrier due to the adsorption of chemicals is ruled out.…”
Section: Introductionsupporting
confidence: 86%
See 2 more Smart Citations
“…Such an effect is particularly evident for methanol where a 15% enhancement of the fast decay time has been measured. The results are fully compatible with a model we recently suggested [8,16,18] based on the saturation effect of the QD non-radiative surface states by the vapour organic molecules. The model suggested is here experimentally confirmed for the first time while the alternative explanation of an off-set of the air potential barrier due to the adsorption of chemicals is ruled out.…”
Section: Introductionsupporting
confidence: 86%
“…In previous studies [8,[15][16][17][18] we investigated the chemical sensitivity of InP/InGaP SQDs. We found that the composition of the surrounding gaseous environment strongly affects their PL intensity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CQDs showed UV absorption at about 346 nm and a broad spectrum of photoluminescence with quantum yield of 49.9%. Roberta De Angelis et al [9] investigated the Chemical Sensitivity of Luminescent Epitaxial Surface InP Quantum Dots, where a broad-band near-infrared photoluminescence ranging from 750 to 865 nm was reported from the surface InP quantum dots grown by gas source molecular beam epitaxy on In 0.48 Ga 0.52 P buffer layer lattice matched to GaAs substrate. When the quantum dots exposed to vapors of different chemical solvents with the highest sensitivity for alcohol (methanol and ethanol) vapours a reversible luminescence intensity enhancement has been observed.…”
Section: Introductionmentioning
confidence: 99%
“…This happens as a consequence of the change in the density of states as a result of spatial confinement [2]. In addition, the nano-size provides the semiconductor nanocrystals with a high surface area which is a relevant condition for adsorption of the analyte vapour [3][4][5][6]. The process of the analyte detection on the semiconductor surface is usually due to the changes in the band bending or surface recombination velocity caused by the bound species from the analytesubstrate surface states interactions.…”
Section: Introductionmentioning
confidence: 99%